Expanding Brackets (single and double)

Easy

Medium

Difficult

Q1) 5(5z -2) =
Q1) \((x + 2)(x + 8)\)
Q1) \((6x + 6)(8x + 1)\)
Q2) 5(4y + 2) =
Q2) \((x + 4)(x + 6)\)
Q2) \((2x + 5)(8x + 2)\)
Q3) 3(5z + 5) =
Q3) \((w + 7)(w + 7)\)
Q3) \((10x + 1)(7x -2)\)
Q4) 3(5z -2) =
Q4) \((x + 1)(x + 6)\)
Q4) \((3x + 3)(4x -4)\)
Q5) 2(4y + 4) =
Q5) \((x + 9)(x + 5)\)
Q5) \((3x + 4)(6x -2)\)
Q6) 2(4z + 2) =
Q6) \((w + 8)(w + 7)\)
Q6) \((3x + 6)(9x + 2)\)
Q7) 3(4z -9) =
Q7) \((y + 3)(y + 6)\)
Q7) \((8x + 5)(8x + 2)\)
Q8) 4(3y -2) =
Q8) \((x + 9)(x + 6)\)
Q8) \((8x + 1)(10x -2)\)
Q9) 5(2y + 4) =
Q9) \((y + 9)(y + 1)\)
Q9) \((8x + 4)(7x + 3)\)
Q10) 4(2z -6) =
Q10) \((z + 7)(z + 2)\)
Q10) \((8x + 6)(4x + 3)\)